Intracoronary Levosimendan during Ischemia Prevents Myocardial Apoptosis - Malmberg, Markus; Vähäsilta, Tommi; Saraste, Antti; Koskenvuo, Juha; Pärkkä, Jussi; Leino, Kari; Laitio, Timo; Stark, Christoffer; Heikkilä, Aira; Saukko, Pekka; Savunen, Timo (Frontiers in Physiology, 2012)
Background. Levosimendan is a calcium-sensitizing inotropic agent that prevents myocardial contractile depression following cardiac surgery. Levosimendan has also anti-apoptotic properties, but the role of this mechanism is not clear. We studied whether levosimendan prevents cardiomyocyte apoptosis and post-operative stunning after either intracoronary administration or intravenous infusion in an experimental model. Methods. Pigs (n=24) were subjected to 40 minutes of global, cardioplegic ischemia under cardiopulmonary bypass and 240 minutes of reperfusion. L-IV group received intravenous infusion of levosimendan (65 μg/kg) 40 minutes before ischemia and L-IC group received levosimendan (65 μg/kg) during ischemia administered intracoronary. Control group was operated without levosimendan. Echocardiography was performed to all animals. Apoptosis was determined from transmyocardial biopsies taken from left ventricle using TUNEL assay and immunohistochemistry of active caspace-3. Results. Apoptosis was induced after ischemia-reperfusion in all groups (pre L-IV 0.002±0.004 % vs. post L-IV 0.020±0.017 % p=0.02, pre L-IC 0.001±0.004 % vs. post L-IC 0.020±0.017 % p<0.001, pre control 0.007±0.013 % vs. post control 0.062±0.044 % p=0.01). The amount of apoptosis was higher in the controls, compared with the L-IV (p=0.03) and the L-IC (p=0.03) groups. Longitudinal left ventricular contraction was significantly reduced in the L-IC and the control groups when compared to the L-IV group (L-IV 0.75±0.12 mm vs. L-IC 0.53±0.11 mm p=0.003, L-IV vs. control 0.54±0.11 p=0.01). Conclusions. Both intracoronary administration and pre-ischemic intravenous infusion of levosimendan equally prevented apoptosis, but intravenous administration was required for optimal preservation of the post-operative systolic left ventricle function.